2013
DOI: 10.1002/ddr.21095
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Microbiome: Insights for Personalized Medicine

Abstract: The large scope of the human microbiome and its interactions with host tissues is currently unfolding. The complex interactions of the human microbiome with the human metabolome and epigenome may affect the susceptibility to and severity of complex diseases that include metabolic disorder, cancer and CNS disease states. In addition, the individual microbiome may modulate drug pharmacokinetics (PK) and pharmacodynamics (PD), contributing to drug response variations between individual patients. Current knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The convergence of personalized medicine and awareness about the human microbiome has naturally led to efforts to identify microbial factors associated with clinical outcomes 15 . Important studies have shown that configuration of the microbiota can be linked to tumor responsiveness during chemotherapy 3,16 , survival after stem cell transplantation 17 , and weight loss after Roux-en-Y gastric bypass 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The convergence of personalized medicine and awareness about the human microbiome has naturally led to efforts to identify microbial factors associated with clinical outcomes 15 . Important studies have shown that configuration of the microbiota can be linked to tumor responsiveness during chemotherapy 3,16 , survival after stem cell transplantation 17 , and weight loss after Roux-en-Y gastric bypass 18 .…”
Section: Discussionmentioning
confidence: 99%
“…2 The symbiotic relationship that coevolves over time bestows humans with functions that do not need to be encoded within their own genomes, or at least not completely, 3 and contributes to interindividual differences. 4,5 The gut microbiome not only has been correlated with disorders such as inflammatory bowel diseases (IBD), obesity, and diabetes [6][7][8] but has also been shown to have extended effects in other, distant organs, including autism spectrum disorder and Alzheimer disease, 9,10 conditions previously thought irrelevant to gastrointestinal bacteria, thus heralding a new era of microbiome studies.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacogenomics does not consider environmental influences on drug pharmacokinetics (absorption, distribution, metabolism, excretion) and/or pharmacodynamics — neither the role of gut microbiome ( Walter and Ley, 2011 , Gurwitz, 2013 , Li and Jia, 2013 ). More recently, in an alternative, but yet complementary discipline, pharmacometabolomics aims to predict and/or evaluate drug metabolism ( Everett, 2015 , Nicholson et al, 2011 ).…”
Section: Pharmacometabolomics In Precision Medicinementioning
confidence: 99%